Pengaruh Motivasi Kerja Terhadap Kinerja Karyawan Bagian Produksi (Studi Pada PT. Mitratani Dua Tujuh, Jember) (Jurnal Strategi dan Bisnis, 2023)
This study aims to explain the effect of work motivation on the performance of production employees at PT. Mitratani Dua Tujuh, Jember. This type of research is quantitative research with a positivistic approach. The population of this research is the permanent employees of the production division of PT. Mitratani Dua Tujuh, Jember in 2022. The number of samples for this research is 50 respondents. The data collection tchnique used is a questionnaire. Testing this research instrument using the validity test and reliability test. Analysis of the data used is multiple linear regression analysis with the F test and T test. The results of the T test and F test show that the work motivation variable has a significant positive effect of 0.000 on the performance of employees at PT. Mitratani Dua Tujuh, Jember. The coefficient of determination in this study shows that the value of R Square is 0.590, meaning that work motivation has an effect of 59% on employee performance. The results of the descriptive data analysis show that the highest score is X_1 worth 222 about harmonious interaction between fellow employee and Y_10 worth 228 about work done in a disciplined manner, the lowest score is X_6 worth 195 about praise given in accordance with personal performance appraisal and Y_5 worth 195 about quality of work better than other colleagues. Keywords: Work Motivation and Employee Performance